The Effect Of Learning Environment And Students Independent Learning On Students Learning Outcomes - Agustina Setyaningsih; Nur Kholik; Achmad Abdul Azis; Tri Yusnanto; Abdurrahman Sadikin (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study intends to evaluate school students' learning outcomes in mathematics classes in terms of learning independence and learning environment. One of schools served as the research site. This study uses survey methods for data collecting and is a quantitative descriptive study. The findings revealed that: The average score for student learning outcomes in mathematics courses is lower than the school's KKM score. Student learning results in mathematics classes are somewhat affected favorably and significantly by student learning freedom. Student learning results in mathematical learning areas are significantly and positively impacted by the student learning environment. Student learning results in mathematics are concurrently influenced by the learning environment and student autonomy.